Working identity : unconventional strategies for reinventing your career - Ibarra, Herminia, 1961- (Harvard Business Review Press, 2023)
"Whether as a daydream or a spoken desire, nearly all of us have entertained the notion of reinventing ourselves. Feeling burned out at work, unfulfilled, or just plain unhappy with whatever we're doing, we long to make the leap to a new and different career path. But how do we make this transition successfully? In this update of the much-loved classic, bestselling author Herminia Ibarra presents a model for career reinvention that flies in the face of everything we've learned from "career experts"-and is tailor-made for changing careers in today's uncertain world. Career transition is not a linear path toward some predetermined identity, according to Ibarra; it is a crooked journey along which we try on a host of "possible selves" we might become. Successful reinvention comes not from deciphering and analyzing our past but from inventing and testing our possible futures. Based on in-depth research and updated with new examples of people in different stages of a career transition, Ibarra identifies the three critical strategies-experiment with new professional activities and identities, interact in new networks of people, and make sense of what is happening to us in light of emerging possibilities-that all successful career-changers use. She shows readers how to implement these strategies, with specific advice for how to: Explore possible selves; craft and execute "identity experiments"; create "small wins" that keep momentum going; connect with role models and mentors who can ease the transition; and arrange new learnings into a coherent story of who we are becoming. A call to the dreamer in each of us, Working Identity redefines the process for crafting a more fulfilling future. Where we end up may surprise us"--